Pengaruh Lingkungan Kerja dan Penghargaan Terhadap Produktivitas Kerja Pegawai Perum Perhutani KPH Garut - Danti Putri (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2023)
The problem of employee work productivity is still faced by many companies in the public sector which generally include government agencies and State-Owned Enterprises (BUMN). One of the BUMN companies that has work productivity problems is Perum Perhutani KPH Garut. This study aims to obtain findings related to (1) a description of the work environment, (2) a description of rewards, (3) the level of work productivity, (4) the influence of the work environment on work productivity, (5) the effect of rewards on work productivity, (6) the influence work environment and appreciation of work productivity. This research uses quantitative methods. The sample technique used is a saturated sample of 78 employees. The analysis technique used is Partial Least Square (PLS) using smartPLS computer software version 3.0. The results of the study show that 1) the work environment is at a very appropriate level, 2) the rewards are at a good level, 3) work productivity is at a high level, 4) the work environment has an influence of 47.9% on work productivity, 5 ) rewards have an effect of 45.5% on work productivity, and 6) work environment and rewards have an effect of 78.2% on work productivity From research on hypothesis testing it can be seen that the work environment and rewards have an influence on work productivity.